2024
DOI: 10.1021/jacs.3c12984
|View full text |Cite
|
Sign up to set email alerts
|

Materials Genes of CO2 Hydrogenation on Supported Cobalt Catalysts: An Artificial Intelligence Approach Integrating Theoretical and Experimental Data

Ray Miyazaki,
Kendra S Belthle,
Harun Tüysüz
et al.

Abstract: Designing materials for catalysis is challenging because the performance is governed by an intricate interplay of various multiscale phenomena, such as the chemical reactions on surfaces and the materials' restructuring during the catalytic process. In the case of supported catalysts, the role of the support material can be also crucial. Here, we address this intricacy challenge by a symbolic-regression artificial intelligence (AI) approach. We identify the key physicochemical parameters correlated with the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Catalysts with modified SBA-15, particularly those with Ti, exhibited enhanced acetate production, reaching up to 1.2 mM, compared to the unmodified SBA-15 (Co/SBA-15). As methanol plays a crucial role in the metabolic pathway as a methyl donor, CO 2 hydrogenation was further investigated through a machine learning (ML) approach to enhance methanol selectivity . The Sure-Independence Screening and Sparsifying Operator model suggested that the reducibility of Co and the adsorption strength of intermediates are the primary features.…”
Section: Solid Catalyst Development Strategies For Co2 Fixationmentioning
confidence: 99%
“…Catalysts with modified SBA-15, particularly those with Ti, exhibited enhanced acetate production, reaching up to 1.2 mM, compared to the unmodified SBA-15 (Co/SBA-15). As methanol plays a crucial role in the metabolic pathway as a methyl donor, CO 2 hydrogenation was further investigated through a machine learning (ML) approach to enhance methanol selectivity . The Sure-Independence Screening and Sparsifying Operator model suggested that the reducibility of Co and the adsorption strength of intermediates are the primary features.…”
Section: Solid Catalyst Development Strategies For Co2 Fixationmentioning
confidence: 99%
“…However, the high time cost of the calculations and the low accessibility of the calculated results to experimental researchers is a barrier to the application of ML models in catalyst development. In this respect, it is more cost-effective and versatile to use readily accessible atomic properties as input features. , …”
Section: Introductionmentioning
confidence: 99%